Ectopic eruption of the first permanent molar: Predictive factors for irreversible outcome - Chen, Xinlei; Huo, Yuanyuan; Peng, Yiran; Zhang, Qiong; Zou, Jing (American journal of orthodontics and dentofacial orthopedics, 2021)
The present study aimed to analyze possible factors involved in irreversible (IRR) ectopic eruption (EE) of the first permanent molar and explore potential predictors for the IRR outcome. Children aged 4-11 years, with at least 1 EE and who took their first panoramic radiograph before the age of 8 years, were selected in this study. The subjects were assigned to the self-correcting (SC) and IRR groups. Patients’ age, sex, distribution of EE, and accompanying dental anomalies were recorded. Eruptive angulation (EA) of the first permanent molar, the grade of root resorption in the second deciduous molar, the magnitude of impaction index (MOII), and horizontal distance were measured on the panoramic radiographs. Chi-square tests and independent-sample t test were used for nominal and continuous variables, respectively. The receiver operative characteristic curve was used to determine the critical value. A total of 406 children with 634 first permanent molars, presenting EE, were enrolled, with 61.3% of the teeth in the SC group. Sex of children with EE and distribution of EE were not relevant to the IRR outcome. The presence of supernumerary teeth might be a protective factor for the IRR outcome. The increasing severity of root resorption in the second primary molar indicated an IRR outcome. A higher MOII and a larger EA suggested an IRR outcome with moderate-to-high quality. The horizontal distance exhibited debatable results, with a low predictive quality. Close monitoring and early intervention would benefit children with increasing severity of distal atypical resorption in the second primary molar, higher MOII, and larger EA. •This study explored outcome predictors for ectopic erupted first permanent molar.•This study is the first to apply the magnitude of impaction on panoramic radiographs.•The magnitude of impaction index tended to be a high-quality predictor.•The existence of supernumerary teeth is possibly related to self-correcting outcome.